An assessment of healthcare professionals' knowledge about and attitude towards influenza vaccination in Freetown Sierra Leone: a cross-sectional study - Peter Bai James; Inayat Ur Rehman; Abudulai Jawo Bah; Michael Lahai; Christine Princess Cole; Tahir Mehmood Khan (BMC, 2017)
Abstract Background Vaccinating healthcare professionals against influenza is considered an effective infection control measure. However, there is a low uptake of influenza vaccine among healthcare professionals around the globe. Currently, it is unknown whether healthcare professionals in Sierra Leone are aware of, and have been vaccinated against influenza. Also, there is a paucity of research evidence on their level of knowledge and attitude toward influenza vaccination. This study assessed healthcare professionals' current influenza vaccine uptake rate, reasons for not getting vaccinated as well as their awareness, knowledge of, and attitude towards influenza vaccination in Freetown Sierra Leone. Method A cross-sectional study was conducted between February and April 2016 among healthcare providers working in four public and two private health facilities in Freetown Sierra Leone. Linear regression analysis, one-way ANOVA and independent t-test were employed for data analysis. Results Among 706 respondents that participated in the study more than half were females 378 (53.6%), nurses 425 (60.4%), and the majority were between the age group of 20-39 years 600 (85.3%). Only 46 (6.5%) were vaccinated against influenza. Key reasons for not vaccinated against influenza were less awareness about influenza vaccination among HCPs 580 (82.73%) with (β = 0.154; CI 0.058-0.163), the high cost of influenza vaccines and therefore not normally purchased 392 (55.92%) having (β = 0.150; CI 0.063-0.186). More than half believed that HCPs are less susceptible to influenza infections than other people. Also, majority 585 (84.3%) of HCPs thought that influenza disease could be transmitted after symptoms appear. In addition, 579 (83.2%) of HCPs felt that symptoms usually appear 8-10 days after exposure. Close to half 321 (46.0%) of HCPs were not aware of the influenza immunisation guidelines published by the Advisory Committee on Immunization Practices and Centre for Disease Control. Conclusion Influenza vaccine coverage among healthcare professionals in Freetown Sierra Leone was low. High cost, inadequate knowledge about influenza and its vaccine as well as the lack of awareness of vaccine availability were key barriers. Increasing access to influenza vaccine and the use of appropriate educational interventions to increase knowledge and awareness are required to improve influenza vaccination coverage among HCPs.